Reduced frontal activity during a verbal fluency test in fibromyalgia: A near-infrared spectroscopy study. (April 2018) - Chou, Po-Han; Tang, Kuo-Tung; Chen, Yi-Hsing; Sun, Chia-Wei; Huang, Chih-Mao; Chen, Der-Yuan
Highlights: This study examined the brain function using near infrared spectroscopy (NIRS) in Chinese patients with fibromyalgia (FM). We found reduced frontal activity in FM patients compared to healthy individuals. We found reduced frontal activity was associated with severities of depression in FM patients. Abstract: Fibromyalgia (FM) is a complex disorder characterized by widespread chronic pain and associated sleep problems and cognitive dysfunction. However, only few studies focusing on cognitive dysfunction in FM are available so far. In the present study, we aimed to use near infrared spectroscopy (NIRS) to evaluate the brain function in FM patients subjected to a verbal fluency test (VFT). A total of 11 primary FM patients and 13 healthy individuals (HC) underwent NIRS while performing a VFT. The Fibromyalgia Impact Questionnaire (FIQ) was used to evaluate the symptom severity of FM and Beck Depression Inventory II (BDI) was used to evaluate the severities depression symptoms in study participants. Five regions of interests (ROIs) were defined: the frontal-, bilateral inferior frontal gyrus (IFG), and temporal regions. Brain activities of ROIs between the two groups were compared. In addition, we investigated the relationship between clinical symptoms and brain cortical activity in FM patients. Our results showed that there were no significant differences between HC and FM patients in age, sex, and BDI scores. We found significantly reduced brain activity over the frontal regions during a VFT in FM patients (p = .026). In addition, we found decreased frontal activity was associated with BDI scores (rho = −0.755, p = .007). Furthermore, there were no significant correlations between frontal activity and FIQ subscales. In conclusion, our study demonstrated a reduced frontal cortical activity during VFT in FM patients, and that NIRS could be a potential tool for evaluating brain function in FM patients in clinical settings.